Active Learning, Content Focus and Teacher Development Based on TIMSS 2022 in Georgia - Chumburidze, Manana; Setiabudi, Edy; Vassiliadou, Maria; Hasanov, Rovsen; Duangpaserth, Khamphone (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study investigates the relationships between active learning, teacher professional development, and content-specific pedagogical knowledge (Content Focus) in shaping mathematics achievement, utilizing data from the 2022 Trends in International Mathematics and Science Study (TIMSS) for Georgia. Methodology: Employing a quantitative research design, data were collected from 194 teachers through structured questionnaires to examine the interplay between these instructional strategies. Main Findings: The findings revealed acceptable psychometric properties for all constructs, with moderate but statistically significant relationships among the variables. Content Focus demonstrated a critical role in supporting mathematics outcomes, highlighting its potential as a mediating or moderating factor in instructional effectiveness. Despite the lack of significant path coefficients, the results underscore the complexity of educational processes, suggesting that contextual and mediating factors may influence the observed outcomes. Novelty/Originality of this study: This research contributes to the understanding of how pedagogical strategies and content knowledge intersect to improve mathematics achievement, offering actionable insights for policymakers and educators aiming to refine instructional practices and professional development programs.